2011
DOI: 10.1108/00368791111116366
|View full text |Cite
|
Sign up to set email alerts
|

Research on wear characteristics of AISI 1035 steel boronized at various parameters

Abstract: Purpose -This paper aims to research the tribological features of AISI 1035 steel, boronized at various parameters. Design/methodology/approach -The samples were boronized via box boronizing method. By using Ekabor 2 powders, boronizing was conducted at 840, 880, 920, 960 and 1,0008C for two, four and six hours. Wear resistance of boronized samples at determined parameters were analysed. Wear experiments were conducted under 40 N constant load at pin-on-disk experiment setup. Also, microstructures and microhar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…One (either FeB or Fe 2 B) or two (both FeB and Fe 2 B) boride phases may therefore be expected to form in a coating on the surface of any solid iron, alloy or steel substrate in the course of its thermochemical boriding, depending on temperature-time conditions and a source of boron employed. It is indeed observed experimentally (see, for example, [1][2][3][4][5][6][7][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…One (either FeB or Fe 2 B) or two (both FeB and Fe 2 B) boride phases may therefore be expected to form in a coating on the surface of any solid iron, alloy or steel substrate in the course of its thermochemical boriding, depending on temperature-time conditions and a source of boron employed. It is indeed observed experimentally (see, for example, [1][2][3][4][5][6][7][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]).…”
Section: Introductionmentioning
confidence: 79%
“…Comparison of angles 2θ and spacing d of experimental X-ray patterns obtained with the literature data for iron and chromium borides [50][51][52][53][54][55] indicated that in the case of 5-15% Cr alloys and a 13% Cr steel the outer boride layer bordering the boriding agent is a solid solution based on the FeB chemical compound, Table 1 for a Fe-5% Cr alloy as an example [48,49]. It is the first type of their microstructure, which is usually observed with steels [1][2][3][4][5][6][7][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Chromium content of the layers is rather significant.…”
Section: Phase Identity and Chemical Composition Of Boride Layersmentioning
confidence: 99%
“…EDS mapping analysis for the abrasive wear condition for the lower wear coefficient (0.98 N and 0.5 g cm −3 ) at the end of the test confirm that the niobium boride layer is completely smeared-off (as shown in figure 9). It can be seen an increase in the presence of oxygen atoms inside the wear crater region, despite the good oxidation resistance of the iron boride phases [49,50]. There is less amount of oxygen in the sample surface, which indicates that the niobium boride layers can be used as oxidation protection coatings [51].…”
Section: Tribological Behaviormentioning
confidence: 99%
“…Gupta et al (1995) proposed the following correlation for the prediction of erosion rate: where E W is designated for erosion rate, “V” velocity, “d” particle size, “C” is slurry concentration, whereas K, α , β and γ are designated for various constants whose magnitudes depend on the target material and erodent properties. Furthermore, considerable research studies have been conducted in the past to understand the mechanism of wear of uncoated and coated members (Dogan et al 2003 and Kiratli and Findik, 2011).…”
Section: Introductionmentioning
confidence: 99%